RESEARCH FOR RATIONAL USE AND PROTECTION OF THE NATURAL ENVIRONMENT - Stupen Н.; Kotyk З.; Vanchura Р.; Smolii К. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
The article supplies an analytical review of publications on application of the research for rational use and protection of the natural environment. It is noted that peculiarities of geographical position, natural conditions (topography, water and forest resources, agricultural lands) as well as features of the historical development have caused significant territorial differences in rural settlements, sizes and types of villages. At the current stage of social development, it is necessary to study the issue of human and nature interaction, to analyze the effects of that interaction and to develop environmental measures. The work gives a brief analysis of the methods of territory organization and substantiates that land use should consider ecological requirements, particularly soils, relief, pollution of the area, as well as restriction caused by the landscape peculiarities and the measures of development and reclamation of agricultural lands. The search for the rational use and protection of the environment is carried out as a part of complex engineering surveys in order to: assess the current state of the main components of the environment (lithosphere, hydrosphere, atmosphere, biosphere) for further consideration in the project; develop materials for assessing the impacts and economic activities on the environment in the design documentation, for new construction reconstruction, technical re-equipment or liquidation of facilities in accordance with DBN A.Z.Z-1; forecast possible changes while preserving existing trends and planned impacts; detect geopathogenic zones; develop recommendations on regulation of impacts, engineering training of the developed (developed) territory and features of structures of buildings and structures, as well as recommendations for creating favorable environmental conditions; elaborate measures for environmental protection. The composition of the surveying works is determined depending on: purpose assignment of works; degree of study of the territory (including prescription of information); nature and extent of changes in the conditions of natural components, the degree of degradation of the environmental components. Methods of surveying on each component are regulated by the relevant regulatory documents. In difficult environmental conditions, before performing work, it is necessary to involve specialized organizations or use information from their funds. The analysis of information should be carried out by a sophisticated organization according to the purpose of the work.